Pulmonary Hypertension in Adults with Congenital Heart Disease (ACHD): Case Study of Undetected Atria Septal Defect - Bulbulia, Bashir Ahmed; Essop, Anisa R (British Journal of Healthcare and Medical Research, 2025)
Patients with Congenital Heart Diseases (CHD) in developed economies reach adulthood (ACHD) due to early detection and medical advances. CHD may go undetected in developing nations during early childhood and present in later years as a result of complications. These include pulmonary hypertension (PH), right heart failure, atrial fibrillation, and stroke resulting from congenital heart conditions such as atrial (ASD) /ventricular septal defects (VSD). These debilitating illnesses have a high morbidity and mortality. A significant dilemma is the optimal management of patients with ASD complicated by PH. Echocardiography, with Right(R) and Left(L) heart studies are essential in evaluating these conditions. Therapeutic advances and newer pharmacological agents have improved survival in patients with PH. Failure of medical treatment may require surgical intervention. Operability and repair require expert opinion and specialist assessment. Lung transplant and closure of the ASD are remaining options.